Russian Crime of the Past Decade: Is the Time of Illusions Over? - Bakharev, Dmitry V.; Gamanenko, Leonid I.; Musharatsky, Mikhail L.; Ustinov, Andrey A. (International Journal of Criminology and Sociology, 2021)
The purpose of the study is by analyzing the state and dynamics of crime in Russia over the past decade (2010-2020): 1) to identify the factors that influenced the criminal activity of the Russian population during this period; 2) determine the main directions of the then implemented state criminal policy; 3) assess its effectiveness. Research methods: method of summary and grouping of statistical observation materials, analysis of absolute and relative values (structure, intensity and dynamics), analysis of series of dynamics. The results of the study indicate that, since 2015, there has been a progressive increase in crime in Russia, due to unfavorable trends in the development of the socio-economic sphere. During this period, there was also a significant discrepancy between the data of official crime statistics and the real situation in the field of crime. This discrepancy was due to large-scale transformation processes taking place in the sphere of the state’s criminal policy. Accordingly, the decrease in the amount and level of official crime in Russia in 2016-2018 was a consequence of these processes, while the real crime continued to grow all these three years. However, the sharp increase in crimes against property committed through the use of information and communication technologies, which began in Russia several years ago, ultimately could not but be reflected in the data of official crime statistics – in the past two years, an increase in both the amount and the level of crime has been recorded in the state. Russian law enforcement agencies have so far shown their unwillingness to offer serious resistance to digital crime. Russian law enforcement agencies have so far demonstrated their unwillingness to offer serious resistance to digital crime. The situation is significantly complicated by the fact that a significant part of crimes in the sphere of information and communication technologies is committed by inmates of Russian prisons. This means that today, in addition to a strong external influence from the criminal environment, the country’s law enforcement system is also experiencing a powerful endogenous influence from the criminals who are already serving their sentences in prisons.